SARS-CoV-2: Impact on, Risk Assessment and Countermeasures in German Eye Banks. (4th May 2021) - Trigaux, Céline; Salla, Sabine; Schroeter, Jan; Tourtas, Theofilos; Thomasen, Henning; Maier, Philip; Hellwinkel, Olaf J.C.; Wittmershaus, Ilka; Merz, Patrick R.; Seitz, Berthold; Nölle, Bernhard; Schrage, Norbert; et al.
ABSTRACT: Introduction: Since the beginning of the COVID-19 pandemic there has been some debate regarding the risk of transmission through tissue transplantation and tissue banking processes. Aim of the study: To analyze the changes that SARS-CoV-2 has caused regarding the harvesting of corneal donor tissue and eye bank activities in Germany. Methods: A questionnaire was provided to 26 eye banks in Germany, consisting of questions about adaptations made in the screening of potential donors and the harvesting of corneal tissue following the pandemic spread of SARS-CoV-2. Results: Eighteen eye banks actively reduced recruitment of donors and two banks ceased all activity. Additional diagnostic screening was performed in eight banks, using conjunctival swabs and/or nasopharyngeal swabs. In six eye banks, additional protective measures, such as FFP2 masks and/or facial shields, were implemented. Overall, a mean reduction in the number of obtained donor tissues of 17% was observed. Discussion: Conjunctival and/or nasopharyngeal swabs of donors have been implemented by a minority. Reasons for not performing additional tests may be moderate sensitivity and lack of validation for postmortem use of RT-PCR testing. Also, the hazard of SARS-CoV-2 entering the corneal donor pool with subsequent transmission might be perceived as theoretical. Face shields provide a sufficient barrier against splash and splatter contamination but may be insufficient against aerosols. Additional face masks would provide support against aerosols, but it remains debatable if corneal harvesting can be considered an aerosol-producing procedure. In the future we expect to see changes in current guidelines because of a surge in scientific activities to improve our understanding of the risks involved with cornea donation in the COVID-19 pandemic, and because current practice may reduce the availability of donor corneas due to new exclusion criteria while the demand remains unchanged.